Rare presentation of Wegener’s granulomatosis in the pituitary gland: Case report and literature review - Baird, Samantha M. (Int J Surg Case Rep, 2017)
INTRODUCTION: Wegener’s granulomatosis (WG) is a systemic vasculitis that can affect a variety of organs including ear, nose and throat, lungs and kidneys. However WG is unusual in the pituitary and rare in the central nervous system. PRESENTATION OF CASE: A 56-year-old male with likely WG presented with polyuria and polydipsia despite six months of conservative medical management. MRI scanning revealed an enlarging heterogeneously enhancing pituitary gland. Following endoscopic transsphenoidal pituitary biopsy and debulking, final tissue pathology was diagnostic for WG in the pituitary gland. DISCUSSION: Diagnosis remains difficult but most patients present with central diabetes insipidus (CDI) as well as varying degrees of hypopituitarism on a background of disease activity in other organs. Clinical judgment needs to balance the need for invasive surgical tissue diagnosis with increasing immunosuppressive therapy. CONCLUSION: It is important to consider this rare complication of WG to ensure timely diagnosis and management.